A genome-wide association study of rheumatoid arthritis without antibodies against citrullinated peptides. Issue 3 (14th February 2014) - Bossini-Castillo, L; de Kovel, C; Kallberg, H; van 't Slot, R; Italiaander, A; Coenen, M; Tak, P P; Posthumus, M D; Wijmenga, C; Huizinga, T; van der Helm-van Mil, A H M; Stoeken-Rijsbergen, G; et al.
Abstract : Introduction: Rheumatoid arthritis (RA) patients can be classified based on presence or absence of anticitrullinated peptide antibodies (ACPA) in their serum. This heterogeneity among patients may reflect important biological differences underlying the disease process. To date, the majority of genetic studies have focused on the ACPA-positive group. Therefore, our goal was to analyse the genetic risk factors that contribute to ACPA-negative RA. Methods: We performed a large-scale genome-wide association study (GWAS) in three Caucasian European cohorts comprising 1148 ACPA-negative RA patients and 6008 controls. All patients were screened using the Illumina Human Cyto-12 chip, and controls were genotyped using different genome-wide platforms. Population-independent analyses were carried out by means of logistic regression. Meta-analysis with previously published data was performed as follow-up for selected signals (reaching a total of 1922 ACPA-negative RA patients and 7087 controls). Imputation of classical HLA alleles, amino acid residues and single nucleotide polymorphisms was undertaken. Results: The combined analysis of the studied cohorts resulted in identification of a peak of association in the HLA-region and several suggestive non-HLA associations. Meta-analysis with previous reports confirmed the association of the HLA region with this subset and an observed association in the CLYBL locus remained suggestive. The imputation and deep interrogation of the HLA region led to identification of a two amino acid model (HLA-B at position 9 and HLA-DRB1 at position 11) that accounted for the observed genome-wide associations in this region. Conclusions: Our study shed light on the influence of the HLA region in ACPA-negative RA and identified a suggestive risk locus for this condition.